Cost analysis of the Communication and Low Mood (CALM) randomised trial of behavioural therapy for stroke patients with aphasia - Humphreys, Ioan; Thomas, Shirley A.; Phillips, Ceri; Lincoln, Nadina (SAGE, 2015)
Objective: To evaluate the cost effectiveness of a behavioural therapy intervention shown to be clinically effective in comparison with usual care for stroke patients with aphasia.